POSIADANIE A WŁASNOŚĆ NAD UWAGAMI ŚW. TOMASZA - Longchamps de Bérier, Franciszek (Zeszyty Prawnicze, 2017)
POSSESSION AND PROPERTY ON THE REMARKS OF ST. THOMAS AQUINAS Summary There are at least two of St. Thomas Aquinas’s questions which are of interest to a lawyer: whether possession is natural to a human being, and whether the keeping of goods as one’s property is allowable. He gives two positive answers which in general follow Aristotelian arguments. Aquinas is convinced that the natural need for goods does not exclude the acceptability of the institution of property. It would seem that its legal protection is necessary for purely pragmatic reasons which, however, entails certain postulates concerning the use of property, e. g. that an owner should be aware of the social mortgage on his goods. This utilitarianism not only leads a government to protect private property, but also entitles it to intervene when owners behave in a socially unacceptable way.